2004
DOI: 10.1111/j.0014-3820.2004.tb00419.x
|View full text |Cite
|
Sign up to set email alerts
|

Age-Specific Reproductive Success: Evidence for the Selection Hypothesis

Abstract: Abstract. Age-specific reproductive success has been demonstrated in many species. Three hypotheses have been raised to explain this general phenomenon: the experience hypothesis based on age-specific reproductive experience, the effort hypothesis based on age-specific reproductive effort, and the selection hypothesis based on progressive disappearance of phenotypes due to variation in individual productivity and survival. We used data from a long-term study of Leach's storm-petrels (Oceanodroma leucorhoa) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
62
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(68 citation statements)
references
References 61 publications
6
62
0
Order By: Relevance
“…This has also been documented in avian species (Annett & Pierotti 1999, Mauck et al 2004). For example, Mauck et al (2004) found that the Leach's storm petrels which were most successful in the first 2 breeding attempts tended to live longer and have higher lifetime reproductive success.In addition to maternal traits influencing dive behavior, there were significant differences in diving behavior between the 2 years of the study and as the season progressed (Tables 1, 2, & 3). All the females from the 2005 season, except one primiparous female, clustered into one group (Fig.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…This has also been documented in avian species (Annett & Pierotti 1999, Mauck et al 2004). For example, Mauck et al (2004) found that the Leach's storm petrels which were most successful in the first 2 breeding attempts tended to live longer and have higher lifetime reproductive success.In addition to maternal traits influencing dive behavior, there were significant differences in diving behavior between the 2 years of the study and as the season progressed (Tables 1, 2, & 3). All the females from the 2005 season, except one primiparous female, clustered into one group (Fig.…”
supporting
confidence: 56%
“…This could explain the longer foraging trip durations and greater time spent at sea. The greater variability in foraging effort and diving behavior seen in young females compared to the prime-aged females could also be explained by a higher proportion of lower-quality individuals in the young age classes that have yet to be selected out of the breeding population (Annett & Pierotti 1999, Mauck et al 2004, Beauplet et al 2006. Beauplet et al (2006) found that in sub-Antarctic fur seals there was a higher proportion of low-quality individuals in the lower age classes.…”
Section: Influence Of Maternal Traits and Individual On Foraging Behamentioning
confidence: 99%
“…'good hunters' and 'bad hunters' differentially appeared or disappeared from the population). We therefore tested the prediction of a positive correlation between diet composition of first-time breeding males (proportion of pigeons in diet of first breeding attempt) and longevity (number of years breeding), which is exclusive for the selection hypothesis (Forslund & Pärt 1995;Mauck et al 2004). For this analysis, we had to exclude seven males from the dataset, which had not yet died or emigrated by the end of the study in 1997.…”
Section: Methodsmentioning
confidence: 99%
“…Newton 1989;Martin 1995;Bennet & Owens 2002;Reid et al 2003), although there are also some striking counter claims, for example, in common terns Sterna hirundo ( Nisbet et al 2002; but see Gonzalez-Solis et al 2004) and Leach's stormpetrels Oceanodroma leucorhoa (Mauck et al 2004) where despite reasonable sample sizes, no evidence for a diminution of performance in older individuals was found. It has often been pointed out that, as with early improvement, an age-related decline in mean reproductive performance measured at the population level can be due either to changes within individuals, or in the quality of individuals that are active at different ages, or to a combination of such effects ( Vaupel & Yashin 1985;van de Pol & Verhulst 2006).…”
Section: Introductionmentioning
confidence: 99%